Aid on Demand: African Leaders and the Geography of China s Foreign Assistance - Andreas Fuchs; Axel Dreher; Roland Hodler; Bradley C. Parks; Paul Raschky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate whether the political leaders of aid-receiving countries use foreign aid inflows to further their own political or personal interests. Aid allocation biased by leaders selfish interests arguably reduces the effectiveness of aid, negatively affecting development outcomes. We examine whether more Chinese aid is allocated to the political leaders birth regions and regions populated by the ethnic group to which the leader belongs, controlling for objective indicators of need. We have collected data on 117 African leaders birthplaces and ethnic groups and geocoded 1,955 Chinese development finance projects across 3,553 physical locations in Africa over the 2000-2012 period. The results from various fixed-effects regressions show that current political leaders birth regions receive substantially larger financial flows than other regions. We do not find evidence that leaders shift aid to regions populated by groups who share their ethnicity.
Keywords: D73; F35; P33; 330